Aster oliganthus (Asteraceae, Astereae), a new species from western Sichuan, China, based on morphological and molecular data - Li, Zhi; Yin, Gen-Shen; Tang, Ming; Li, Wei-Ping (Phytotaxa, 2017)
Aster oliganthus (Asteraceae, Astereae), a new species from two populations of the eastern Mt. Hengduanshan region in western Sichuan, China, is illustrated and described. The new species is similar to A. ageratoides in habit, triplinerved leaves, lower and basal leaves withering at anthesis, terminal paniculate-corymbiform to corymbiform synflorescences, and 3–5-seriate phyllaries, but differs from it by falcate leaves with long acuminate to caudate apex, 5–7(–9) ray florets, and (2–)4–5 disc florets. Based on the phylogenetic analysis of internal and external transcribed spacers of nrDNA, we demonstrated that the two populations form a highly supported clade, are closely related to but not nested within the A. ageratoides clade, which supports that A. oliganthus is a good species and belongs to A. subgen. Aster sect. Ageratoides. Cytological observation shows that the new species is diploid with its karyotype being 2n =2x =18 = 16m + 2sm.